DETERMINANTS OF TECHNOLOGY ADOPTION: THE CASE OF DRYLAND FARMER IN LOMBOK Determinasi Adopsi Teknologi: Kasus Petani Lahan Kering di Lombok - Abdullah Usman (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2001)
ABSTRACT Dryland farmers in Lombok underuse the water provided through deep well irrigation pump, far below the optimum level of wateruse. Question raised in this study is what are the determinants factors explaining wateruse level of dryland farmers in Lombok. Therefore, this study aims to identify such determinants factors and by knowing the factors, it can be a valuable consideration in motivating farmers to optimize their wateruse. This study used a two-stage cluster sampling method: (1) to choose pumps by classifying a total of 168 pumps into 23 existing pump groups and (2) to select farmers from each selected pumps. The number of farmers interviewed is 323. To investigate the factors affecting the level of wateruse, linear multiple regression was used. This study revealed that Adopters are significantly different to non-adopters in terms of age, farming experience, hours of extension attended, holding area, farm income, farmer income, household income and cropping intensity. Land status, the frequency of operator change, the access of respondents to part time jobs, migration status and dryland problems are significant at the five percent level or lower. Determinant factors which can be used to explain the phenomenon of under use of water are: price of water, proportion of cash-cost farm income, household income, and hours of attending extension training. Implication of this study is that attempt to motivate farmers in optimizing wateruse can be more effective if we can reduce the water price or find the in-question product market which is provide more reasonable price. ABSTRAK Penggunaan air irigasi pompa artesis oleh petani lahan kering di Pulau Lombok masih jauh dibawah tingkat penggunaan optimum. Masalah yang diangkat dalam kajian ini adalah apa saja yang menjadi faktor penentu didalam menjelaskan tingkat penggunaan air oleh petani lahan kering di Pulau Lombok. Karena itu, kajian ini bertujuan untuk mengidentifikasi faktor penentu yang dimaksud yang dengan memahaminya dapat diupayakan solusi untuk mendorong petani agar mengoptimumkan penggunaan air. Kajian ini menggunakan sampel yang ditentukan dengan metoda cluster dua langkah: (1) untuk menentukan pompa dengan mengkalisifikasikan 168 pompa kedalam 23 group and (2) untuk memilih petani dari masing-masing skim dari pompa yang terpilih. Petani yang diwawancara 323 orang. Untuk memeriksa faktor penentu digunakan regresi berganda. Study ini mengungkapkan bahwa adopter berbeda dengan non adopter dalam hal: umur, pengalaman bertani, penyuluhan, luas areal, pendapatan usahatani, pendapatan rumah tangga dan intensitas tanam. Faktor penentu adopsi teknologi meliputi: harga air, proporsi pendapatan, pendapatan rumah tangga, dan penyuluhan. Implikasi dari penelitian ini adalah bahwa memotivasi petani agar mengoptimumkan penggunaan airnya dapat dilakukan dengan menekan harga air atau mengusahakan pasar produk yang dihasilkan petani lahan kering